Demographic and autopsy characteristics of drowning deaths in a major autopsy center of Gandaki province of Nepal - Baral, Madan Prasad; Subedi, Nuwadatta (Journal of Gandaki Medical College-Nepal, 2021)
Background: Autopsy examination is mandatory in all unnatural deaths as per law of Nepal and thus all deaths due to drowning are undergone medico legal autopsy. This study aims to analyze the demographic and autopsy characteristics of drowning deaths in cases brought for medico legal autopsy at a major autopsy center of Gandaki province of Nepal.Methods: This study was conducted based on review of database in a period of two years among 53 corpses of drowning related deaths. The demographic data and relevant information from the inquest and autopsy report of such cases were collected and presented.Result: The commonest age group involved in drowning deaths was